Os debates do significado de educar para as relações étnico-raciais na educação brasileira - Cruz, Ana Cristina Juvenal da (2010)
This research is to understand the strategies and pedagogical practices employed by teachers to the education of ethnic-racial relations. The research is located within the theoretical studies of race relations and education, has scaled the debate on the race category, education, and action of black movements in the perspective the debate on recognition. The object of work is outlined in part from the projects submitted to the Prêmio Educar para a Igualdade Racial of the CEERT Centro de Estudos das Relações de Trabalho e Desigualdades in editions 2002, 2004, 2006 and 2008 and an interview with a teacher award finalist. The index was compiled from the descriptions made by the teachers of the projects submitted, bearing in mind the articulation with the literature discussed in research with the objective of at understanding how these teachers think the education of ethnic-racial relations in Brazil. It is therefore conceptions of school, culture, diversity, difference between other terms expressed in the proposals. The record of this educational experience indicates the emergence of an education of ethnic-racial relations and suggests the fragility of proposals aimed at racial equality guided democracy and racial progress toward recovery and recognition of differences in perspective.